DBT skills training manual - Linehan, Marsha M.; Linehan, Marsha (New York : The Guilford Press, 2015)
Summary: "From Marsha M. Linehan--the developer of dialectical behavior therapy (DBT)--this comprehensive resource provides vital tools for implementing DBT skills training. The teaching notes and reproducible handouts and worksheets used for over two decades by hundreds of thousands of practitioners have been significantly revised and expanded to reflect important research and clinical advances. The book gives complete instructions for orienting individuals with a wide range of problems to DBT and teaching them mindfulness, interpersonal effectiveness, emotion regulation, and distress tolerance skills. Handouts and worksheets are not included in the book; purchasers get access to a Web page where they can download and print all the handouts and worksheets discussed in a convenient 8 1/2" x 11" size"--Provided by publisher.
Machine generated contents note: List of Online Handouts and Worksheets I. An Introduction to DBT Skills Training 1. Rationale for Dialectical Behavior Therapy Skills Training 2. Planning to Conduct DBT Skills Training 3. Structuring Skills Training Sessions 4. Skills Training Treatment Targets and Procedures 5. Application of Fundamental DBT Strategies in Behavioral Skills Training Part I Appendices II. Teaching Notes for DBT Skills Modules 6. General Skills: Orientation and Analyzing Behavior 7. Mindfulness Skills 8. Interpersonal Effectiveness Skills 9. Emotion Regulation Skills 10. Distress Tolerance Skills Index
Preceded by: Skills training manual for treating borderline personality disorder / Marsha M. Linehan. c1993.
Includes bibliographical references and index..
Keywords: Beteendeterapi; Psykoterapi; Borderline; Psychotherapeutic Processes; Borderline Personality Disorder -- therapy; Behavior Therapy -- methods; Psychotherapy -- methods; Suicide -- prevention & control; Behavior therapy; Psychotherapy; Borderline personality disorder